2018
DOI: 10.1080/01292986.2018.1453849
|View full text |Cite
|
Sign up to set email alerts
|

Predicting elections from social media: a three-country, three-method comparative study

Abstract: This study introduces and evaluates the robustness of different volumetric, sentiment, and social network approaches to predict the elections in three Asian countries-Malaysia, India, and Pakistan from Twitter posts. We find that predictive power of social media performs well for India and Pakistan but is not effective for Malaysia. Overall, we find that it is useful to consider the recency of Twitter posts while using it to predict a real outcome, such as an election result. Sentiment information mined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 28 publications
0
44
0
2
Order By: Relevance
“…On the other hand, a supervised learning approach, which trains sentiment models on a small set of hand-annotated political social media messages, yields much better predictions by inferring sentiments from otherwise neutral words used in context. Furthermore, studies have suggested that discarding negative posts and instead focusing on the positive tweets can help to filter out a large part of the noise from election-related content on social media [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a supervised learning approach, which trains sentiment models on a small set of hand-annotated political social media messages, yields much better predictions by inferring sentiments from otherwise neutral words used in context. Furthermore, studies have suggested that discarding negative posts and instead focusing on the positive tweets can help to filter out a large part of the noise from election-related content on social media [24].…”
Section: Discussionmentioning
confidence: 99%
“…Structural features can also capture the density of online discussions. More decentralized networks have more active users and thus wider outreach to a larger potential voter base [24]. Structural features have been found to be useful to dampen the estimation effects associated with national parties that are over-represented on social media, or regional parties which may be popular online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presidential campaign prediction using Twitter data is a much-discussed research topic and the number of studies are still growing (Awais et al, 2019;Bansal & Srivastava, 2019;Heredia et al, 2018;Jaidka et al, 2019;McGregor et al, 2017;Verma et al, 2019). There is, however, no real benchmarking on the performance (Gayo-Avello, 2013) to identify the best method to determine the winner of the elections or the voting share with the minimum error.…”
Section: Algorithms Comparison With State Of Artmentioning
confidence: 99%
“…to predict consumer behaviour in the real world (Rathor et al, 2018;Volkova et al, 2015). Recently this type of analysis has jumped into the eld of politics in an attempt to predict the results of election campaigns by monitoring the interaction between candidates and voters (Awais et al, 2019;Jaidka et al, 2019;Shmargad & Sanchez, 2020). The fact that more and more people are posting on the OSN had led to researchers and journalists to believe that a collective feeling is present in the OSN, which can be listened to, captured and analysed (Budiharto & Meiliana, 2018;Cury, 2019).…”
Section: Introductionmentioning
confidence: 99%